Written corrective feedback studies: Approximate replication of Bitchener & Knoch (2010a) and Van Beuningen, De Jong & Kuiken (2012). (18th June 2015) - Bitchener, John; Knoch, Ute
Abstract : The question of whether written corrective feedback (CF) has a role to play in second language (L2) development has been controversial since Truscott (1996 ) published an article in Language Learning calling for the abandonment of the practice on theoretical, empirical and pedagogical grounds. As a result of his claims, an on-going debate about the efficacy of the practice has ensued while a number of dedicated researchers have focused their attention on empirically investigating whether learners benefit from the practice in terms of significantly improving their accuracy in subsequent texts over time. Responding not only to Truscott's doubts about the overall effectiveness of written CF for L2 learning and his specific doubts about whether certain types of provision could ever have a meaningful and enduring effect on acquisition, further questions about the potential impact of different variables were central to the thinking and research that followed his claims. Such variables include the linguistic focus of the feedback and the relative merits of targeting a limited number of error categories (focused feedback) rather than a more comprehensive range of error categories (unfocused feedback). While a growing body of research has begun investigating these issues over the last 15–20 years, the field is in need of replication studies before firm conclusions can be reached.